2009
DOI: 10.1002/anie.200805512
|View full text |Cite
|
Sign up to set email alerts
|

The Norbornene Shuttle: Multicomponent Domino Synthesis of Tetrasubstituted Helical Alkenes through Multiple CH Functionalization

Abstract: Shall we dance? Within the proposed mechanism for the palladium-catalyzed title reaction, the strained alkene norbornene (or norbornadiene) enters and exits the catalytic cycle in a catalytic "square dance", acting as both a promoter and a coupling partner in the formation of four carbon-carbon bonds, two of them by challenging C--H activation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(42 citation statements)
references
References 48 publications
0
41
0
1
Order By: Relevance
“…[39] Auch die Verwendung eines Alkylhalogenids, das eine Acetylengruppe enthält, führte zu einer beeindruckenden Synthese vierfach substituierter helicaler Alkene (Schema 24). [40] Interessanterweise gelang Carretero und Mitarbeitern auch eine analoge Form der "Kaskadenkatalyse" zur Arylierung, die ohne Verwendung von Norbornen auskommt (Schema 25). [41] …”
Section: Introductionunclassified
“…[39] Auch die Verwendung eines Alkylhalogenids, das eine Acetylengruppe enthält, führte zu einer beeindruckenden Synthese vierfach substituierter helicaler Alkene (Schema 24). [40] Interessanterweise gelang Carretero und Mitarbeitern auch eine analoge Form der "Kaskadenkatalyse" zur Arylierung, die ohne Verwendung von Norbornen auskommt (Schema 25). [41] …”
Section: Introductionunclassified
“…[54] In addition, the group of Lautens discovered that, in the absence of an adjacent heteroaryl or benzyl group on aryl iodide substrates, vinylpalladiums pecies 81 underwent furtherc arbopalladation of NBE to afford sterically crowded tetrasubstituted helical alkenes 86 through CÀHf unctionalization on the adjacent aromaticr ing (Scheme 23 e). [55] In this case, NBE not only acted as the mediator, but also becamea part of the products.M ore interestingly,i fe nantiopure 80 was applied, an intriguing threefold stereoselectivity was observed in the process:r etention of the central chirality,i nduction of helical chirality (5:1-6.7:1 d.r. ), and exclusively exo-facial selectivity of the NBEi ncorporation step.…”
Section: Scheme22 Intramolecular Dialkylations/intermolecular Terminmentioning
confidence: 99%
“…Recently, the group of Luan reported an elegant domino reaction between 3‐(2‐iodophenyl)‐1 H ‐indoles and tethered bromoalkyl alkynes for the concise assembly of pentacyclic products 85 , which contained an interesting spiroindolenine motif (Scheme d) . In addition, the group of Lautens discovered that, in the absence of an adjacent heteroaryl or benzyl group on aryl iodide substrates, vinylpalladium species 81 underwent further carbopalladation of NBE to afford sterically crowded tetrasubstituted helical alkenes 86 through C−H functionalization on the adjacent aromatic ring (Scheme e) . In this case, NBE not only acted as the mediator, but also became a part of the products.…”
Section: Multifunctional Alkylating Reagentsmentioning
confidence: 99%
“…[1] Obviously, asymmetric cascade reactions that can control the chirality of the product are more attractive. [3] Feringa and co-workers have demonstrated that tetrasubstituted helical alkenes, which possess both central and helical chirality, can be applied to light-driven molecular motors. The reaction can produce tetrasubstituted alkenes which possess helical and/or central chirality.…”
Section: Daiki Hojo Keiichi Noguchi and Ken Tanaka*mentioning
confidence: 99%
“…The reaction can produce tetrasubstituted alkenes which possess helical and/or central chirality. [3] Feringa and co-workers have demonstrated that tetrasubstituted helical alkenes, which possess both central and helical chirality, can be applied to light-driven molecular motors. [4] Therefore helical alkenes are attracting growing interest.…”
mentioning
confidence: 99%